2003
DOI: 10.1038/sj.ijo.0802322
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin is influenced by diet composition and exercise

Abstract: OBJECTIVE: A low-fat, high-carbohydrate diet (r30% of total energy intake as fat) in conjunction with moderate intensity physical activity is widely recommended for weight maintenance and reduction. The aim of this study was to assess the effect of adding daily exercise to a short-term high-carbohydrate diet on fasting and postprandial leptin levels. SUBJECTS: Eight healthy, postmenopausal women aged 6074 y (mean7s.d.) (body mass index, BMI: 26.472.3 kg m À2 ; predicted maximal oxygen uptake: 2972 ml kg À1 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 38 publications
(46 reference statements)
4
32
0
1
Order By: Relevance
“…There is little or no correlation between the two hormones in several postprandial studies (Dagogo-Jack et al, 1996;Sinha et al, 1996;Pratley et al, 1997;Guerci et al, 2000;Herrmann et al, 2001;Poretsky et al, 2001) and this has lead to a revived interest in the influence of other dietary nutrients, including lipids, which have a blunted effect on insulin compared to CHO. Other trials which have shown a decrease in leptin after a fatty meal include lean (Romon et al, 1999) and obese subjects (Imbeault et al, 2001), and where HF test meals have followed high-and low-CHO acclimation (Koutsari et al, 2003). In a study of lean women given three HF (60 en%) or three high-CHO meals over 24 h, leptin continued to rise from an 0800 h nadir on both treatments but the postprandial response was less pronounced following the HF meals (Havel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little or no correlation between the two hormones in several postprandial studies (Dagogo-Jack et al, 1996;Sinha et al, 1996;Pratley et al, 1997;Guerci et al, 2000;Herrmann et al, 2001;Poretsky et al, 2001) and this has lead to a revived interest in the influence of other dietary nutrients, including lipids, which have a blunted effect on insulin compared to CHO. Other trials which have shown a decrease in leptin after a fatty meal include lean (Romon et al, 1999) and obese subjects (Imbeault et al, 2001), and where HF test meals have followed high-and low-CHO acclimation (Koutsari et al, 2003). In a study of lean women given three HF (60 en%) or three high-CHO meals over 24 h, leptin continued to rise from an 0800 h nadir on both treatments but the postprandial response was less pronounced following the HF meals (Havel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our study of lean men showed a decrease in leptin but not ghrelin over 6 h following a HF meal, and an increase in saturation of the fatty meal did not further alter response of either hormone. Since meals rich in SFA reduce postprandial insulin sensitivity (Robertson et al, 2002), and insulin may be an important modulator of leptin (Havel et al, 1999;Evans et al, 2001;Koutsari et al, 2003;Romon et al, 2003;Fogteloo et al, 2004) and ghrelin (Mohlig et al, 2002;Saad et al, 2002;Flanagan et al, 2003), we wanted to determine whether increasing dietary SFA may differentially alter these hormones. Interpretation of the postprandial response of leptin is complicated by diurnal changes in hormone release, driven in part by meal time and/or composition (Schoeller et al, 1997;Fogteloo et al, 2004), with a decline postbreakfast followed by a midnight peak (Sinha et al, 1996;Coleman and Herrmann, 1999;Havel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity may have too remarkable an impact on serum leptin to be eliminated by adjustment in the model. It is generally the main way for a person's energy expenditure, which indirectly regulates leptin (3,28) . Interaction between age, current smoking status and the Western pattern was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of short-term caloric restriction has an effect on acute changes in serum leptin levels that may not be correlated with fat mass loss. 31,32 In the present study, the patients in both study groups were encouraged to consume a diet containing ∼1200 to 1600 kcal/d. However, during the study period, the control of the patients' diet was based on self-report.…”
Section: Current Therapeutic Researchாmentioning
confidence: 99%